Imagens das contradições nas regiões metropolitanas da Paraíba - Júlia Diniz de Oliveira (Confins)
This essay makes a commented analysis of images that present contradictions between the norms and urban practices in the metropolitan regions of the state of Paraiba. This is a discussion based on an academic master's research about the effectiveness of metropolitan regions, as well as their role in territorial management.